Implementación de tecnología cloud computing software como servicio, para el agendamiento de citas médicas en el consultorio médico de la ESPAM MFL - Ozaeta Bermúdez, José Ignacio (2017)
The purpose of this study was to carry out a study on the use of Cloud Computing technologies applicable to the health area, in order to use the Cloud Computing SaaS technology to improve the online medical appointment scheduling process of the Medical Office Of the ESPAM MFL. Within this exploration, data were collected through surveys of students and staff that allowed for statistical analysis. For development, the SaaS life cycle methodology was used, which consists of four phases: requirements, in which an on-site visit to the doctor's office was made to know the appointment scheduling processes; Analysis, the inductive - deductive method was used to determine the tool to be used; Design, the tool was selected in the cloud; Implementation, communication with those responsible for administering Bookitit; Tests, which was performed to verify the operation of the application. The results showed that the use of a medical appointment system was a great contribution to the activities and the allocation of shifts of the doctor's office, in addition to 100% of the patients if they feel benefited with this system.